2011
DOI: 10.1158/1078-0432.ccr-11-0248
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Chemotherapy and Chemotherapy: A New Front against Late-Stage Hormone-Refractory Prostate Cancer

Abstract: Purpose: Stemming from its inherent heterogeneity, single-agent treatments are essentially ineffective against castration-resistant prostate cancer (CRPC). Thus, clinically relevant regimens that harness different modalities to maximize treatment efficacy without increasing cumulative toxicities are urgently needed. Based on this rationale, we investigated whether a novel combination of purine nucleoside phosphorylase–mediated, gene-directed enzyme-prodrug therapy (PNP-GDEPT) with docetaxel against CRPC has su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…42 Furthermore, lowering the level of IL-6 was found to be critical for antitumor activity against prostate cancer by combined purine nucleoside phosphorylase and docetaxel by increasing lymphocyte infiltration, and modulating cytokine levels. 43 We found that tumor-promoting proinflammatory cytokines (IL-1 β , IL-6, and TNF- α ) were decreased, but levels of tumor growth-inhibitory cytokine IL-10 were elevated in spleen and tumor tissues. Concomitantly, we also found that IL-32 β mice, and IL-32 β C and IL-32 β p nude mice had higher levels of CD8 + T cells and CD57 + NK cells in tumor tissues, blood, spleen, and thymus than nontransgenic mice and IL-32 β v mice.…”
Section: Discussionmentioning
confidence: 79%
“…42 Furthermore, lowering the level of IL-6 was found to be critical for antitumor activity against prostate cancer by combined purine nucleoside phosphorylase and docetaxel by increasing lymphocyte infiltration, and modulating cytokine levels. 43 We found that tumor-promoting proinflammatory cytokines (IL-1 β , IL-6, and TNF- α ) were decreased, but levels of tumor growth-inhibitory cytokine IL-10 were elevated in spleen and tumor tissues. Concomitantly, we also found that IL-32 β mice, and IL-32 β C and IL-32 β p nude mice had higher levels of CD8 + T cells and CD57 + NK cells in tumor tissues, blood, spleen, and thymus than nontransgenic mice and IL-32 β v mice.…”
Section: Discussionmentioning
confidence: 79%
“…In order to investigate whether constitutive overexpression of DTX3L, ARTD8 and ARTD9 is associated with mPCa we analyzed their expression levels in the PCa cell lines PC3, DU145 and LNCaP [54-59], and in the normal prostate luminal epithelial cell lines HPE and RWPE1. PC3 and DU145 cells are androgen-refractory mPCa cell lines and are commonly used as CRPC models [60-62]. PC3 and DU145 cells have a high and moderate tumorigenic potential, respectively [58-62], and are highly invasive compared to the poorly tumorigenic LNCaP cells [62-65].…”
Section: Resultsmentioning
confidence: 99%
“…The two widely used PC cell lines PC3 and DU145 are not considered as fully representative of CRPC cells since they were not isolated from prostate cancers that had relapsed after androgen deprivation therapy, and since they express little [5] if any AR [6], whereas AR is often over-expressed in CRPC tumors. However as PC3 and DU145 cells display some of the fundamental properties of a CRPC tumor including high migration (metastasis), androgen-independence and chemo-resistance similar to the CRPC cell line LNCaP C4-2 [7], and also share similar molecular properties, including depletion/mutation of mitochondrial DNA, which have been correlated with invasiveness and drug resistance [8], these two cell lines are frequently referred to as CRPC cells [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%